APOE ε4 carriers may undergo synaptic damage conferring risk of Alzheimer's disease. Issue 11 (16th June 2016) - Sun, Xiaoyan; Dong, Chuanhui; Levin, Bonnie; Crocco, Elizabeth; Loewenstein, David; Zetterberg, Henrik; Blennow, Kaj; Wright, Clinton B.; ,
Abstract: Introduction: Pathogenesis of Alzheimer's disease (AD) in apolipoprotein E ε4 ( APOE ε4) carriers remains unclear. We hypothesize that APOE isoforms have differential effects on synaptic function. Methods: We compared levels of CSF neurogranin (Ng) between APOE ε4 carriers and noncarriers in 399 subjects with normal cognition, mild cognitive impairment (MCI), and AD. We examined associations between Ng levels and age, education, gender, CSF‐Aβ42, and tau protein. Results: Neurogranin levels were significantly higher in APOE ε4 carriers compared to APOE ε4 noncarriers with MCI. Levels of Ng between the APOE ε4 carriers and APOE ε4 noncarriers with AD did not differ. Ng levels were correlated with MMSE and levels of tau and Aβ42. Discussion: Significantly higher CSF Ng levels in APOE ε4 carriers with MCI may reflect synaptic injury underlying early cognitive impairment. Neurogranin may be an early biomarker of AD and important for disease diagnosis and timing of intervention in APOE ε4 carriers.